The talent plan for England. Creating the world's best talent system (Sport England, 2018)
An overview of the talent system England talent pathway What is talent Talent inclusion Talent workforce Talented athletes Talent development Talent development environment Our objectives Our guiding principles Implementing the talent plan Talent development practice Talent research and insight Talent workforce development Talent system investment and initiatives Talent communications Upcoming activity Glossary of terms